Glandular Trichomes and Essential Oil of Thymus quinquecostatus - Ping Jia; Hanzhu Liu; Ting Gao; Hua Xin (The Scientific World Journal)
The distribution and types of glandular trichomes and essential oil chemistry of Thymus quinquecostatus were studied. The glandular trichomes are distributed on the surface of stem, leaf, rachis, calyx and corolla, except petiole, pistil and stamen. Three morphologically distinct types of glandular trichomes are described. Peltate trichomes, consisting of a basal cell, a stalk cell and a 12-celled head, are distributed on the stem, leaf, corolla and outer side of calyx. Capitate trichomes, consisting of a unicellular base, a 1–2-celled stalk and a unicellular head, are distributed more diffusely than peltate ones, existing on stem, leaf, rachis and calyx. Digitiform trichomes are just distributed on the outer side of corolla, consisting of 1 basal cell, 3 stalk cells and 1 head cell. All three types of glandular trichomes can secrete essential oil, and in small capitate trichomes of rachis, all peltate trichomes and digitiform trichomes, essential oil is stored in a large subcuticular space, released by cuticle rupture, whereas, in other capitate trichomes, essential oil crosses the thin cuticle. The essential oil of T. quinquecostatus is yellow, and its content is highest in the growth period. 68 constituents were identified in the essential oils. The main constituent is linalool.